2002
DOI: 10.1007/s00467-002-0865-7
|View full text |Cite
|
Sign up to set email alerts
|

Surface markers of platelet function in idiopathic nephrotic syndrome in children

Abstract: The objective of the study was to investigate platelet activation markers in whole blood in idiopathic nephrotic syndrome (INS) in children. The study group consisted of 34 children with 45 relapses of INS, 35 children in long-term remission of INS, and 26 healthy controls. Using flow cytometry we measured the percentage of platelet microparticles, platelet-platelet aggregates, and surface expression of CD62P (P-selectin) and CD42b (a component of von Willebrand factor receptor). We found an increased percenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 35 publications
(49 reference statements)
2
32
1
Order By: Relevance
“…Sirolli et al [4] found pronounced platelet activation in nephrotic syndrome and suggested that it may contribute to the hypercoagulability of nephrosis. Increased platelet activation in nephrotic syndrome was also found by Tkaczyk and Baj [3] and Kilis-Pstrusinska et al [5]. The analysis of platelet indices revealed small volume (MPV) and differences in size (increased PDW).…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Sirolli et al [4] found pronounced platelet activation in nephrotic syndrome and suggested that it may contribute to the hypercoagulability of nephrosis. Increased platelet activation in nephrotic syndrome was also found by Tkaczyk and Baj [3] and Kilis-Pstrusinska et al [5]. The analysis of platelet indices revealed small volume (MPV) and differences in size (increased PDW).…”
Section: Discussionsupporting
confidence: 51%
“…Patients with heavy proteinuria, hypoalbuminemia, and hypercholesterolemia demonstrate increased concentrations of fibrinogen and C-protein, and a decreased level of antithrombin III [1,2]. There is some evidence that the platelet count (PLT) and state of platelet activation may contribute to the hypercoagulability of nephrosis [3,4,5]. Blood platelets play a crucial role in the pathogenesis of thrombotic changes in various pathological states [6,7,8,9,10,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…We failed to identify any factors with a direct link to vWF activity in nephrotic children. As we have shown previously, the increased release of vWF in early relapse of INS might be caused by platelet activation, but in the following stages of the disease the endothelium might well become its primary source [28]. Importantly, our study does have some limitations since its results might be influenced by selection bias.…”
Section: Discussionmentioning
confidence: 67%
“…A recent study by Tkaczyk and Baj [21] found that compared with agematched healthy controls, children in the acute phase of NS have evidence of platelet activation. Although platelet activation has been associated more with the development of arterial rather than venous thrombosis, studies have also demonstrated the role of platelet activation in venous thromboembolic events [11,22].…”
Section: Discussionmentioning
confidence: 98%